Polityka wobec pamięci versus polityka historyczna: aspekty semantyczny, aksjologiczny i merytoryczny w narracji polskiej - Ponczek, Eugeniusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
Historical policy versus the politics of remembrance is undoubtedly a policy, or a peculiar way to ‘conduct policy,’ where the optimally true knowledge of history as well as falsified and mythicized information about the past are a means to maintain, win and participate in power. By this token, historical policy is about the instrumentalization of the knowledge of history and mythicized accounts or opinions of the past for the sake of the implementation of a politi- cal agenda.So far, the concept of ‘historical policy’ has not yet become a clear academic cate- gory, which makes it difficult to agree what it actually encompasses. Still, the concept of ‘historical policy’ stands a chance of becoming an objective category in political science. Some professional historians may lean towards a certain skepticism, especially if they accept the traditional paradigm of studying the history of society.Misunderstandings regarding the issue of ‘historical policy’ sometimes result in a tendency to reject the possibility of this con- cept being applied by academics from the humanities and social fields of science. Recently, the issue of ‘historical policy’ has become of interest to political scientists, whose area of study involves the multiplicity of ‘detailed policies.’‘Historical policy’ is also discussed by many journalists who do not always present deepened reflections and concrete attitudes, as they rather tend to express their subjective views. It turns out that some Polish historians, po- litical scientists and journalists are embroiled in the current political dispute in Poland. They frequently assume the role of lobbyists or opponents of one option of historical policy or an- other.The issue of historical policy requires analysis and explanation in an objective and multidisciplinary manner. It is a positive phenomenon that more and more publications with academic aspirations are emerging on this subject in Poland. One should recommend the co- operation between political scientists and historians in order to review and reliably explain planned and executed historical policy in a comparative manner.
Politics of remembrance versus historical policy: semantic, axiological and topical aspects in Poland
Keywords: polityka; pamięć; polityka historyczna